Use of pregnancy counselling services in Australia 2007–2012. (February 2015) - Shelley, Julia M.; Kavanagh, Shane; Graham, Melissa; Mayes, Catherine
Abstract Objective: To assess the uptake of Medicare Benefit payments for non‐directive pregnancy support counselling which commenced in November 2006. Methods: Counts of services for pregnancy counselling from 1 July 2007 to 30 June 2012, where a Medicare rebate was paid, were used to calculate age‐, state‐ and provider‐specific rates per 100, 000 women aged 15–44 years, and rates per 100, 000 births for each study year. Results: Rates of Medicare rebates for pregnancy counselling were low, with a mean of 90.6 services per 100, 000 women recorded over the study period. GP services were accessed most frequently, while services provided by allied health professionals averaged less than 5% of those for GPs. The overall rate of services fell in all jurisdictions except Victoria/Tasmania, although services provided by allied health professionals remained steady or rose in all jurisdictions over the study period. Conclusions: There has been a low uptake of pregnancy counselling covered by the Medicare Benefits Item numbers introduced in 2006, especially for services provided by allied health professionals. Due to a lack of available data, the impact on abortion rates is unknown. Implications: Provision of Medicare rebates for pregnancy counselling does not appear to be an effective way of assisting women with unintended pregnancies.